2021
DOI: 10.1007/s10048-021-00662-5
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar ataxias (SCAs) caused by common mutations

Abstract: The term SCA refers to a phenotypically and genetically heterogeneous group of autosomal dominant spinocerebellar ataxias. Phenotypically they present as gait ataxia frequently in combination with dysarthria and oculomotor problems. Additional signs and symptoms are common and can include various pyramidal and extrapyramidal signs and intellectual impairment. Genetic causes of SCAs are either repeat expansions within disease genes or common mutations (point mutations, deletions, insertions etc.). Frequently th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 123 publications
(201 reference statements)
0
16
0
Order By: Relevance
“…In autopsied cases, cerebellar atrophy has been associated with a severe loss in Purkinje cells and degeneration of posterior columns, spinocerebellar tracts, and spinal cord anterior horn cells. 5,6,11,13,14,17 In a recent study, the nonsense mutation W279*, rst reported in association with a Portuguese founder haplotype, was the most frequent mutation, representing 66% of all mutated alleles. 27 During the period of the clinical evolution of AOA1, the rst disease symptoms correlate with poor coordination and ataxia.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In autopsied cases, cerebellar atrophy has been associated with a severe loss in Purkinje cells and degeneration of posterior columns, spinocerebellar tracts, and spinal cord anterior horn cells. 5,6,11,13,14,17 In a recent study, the nonsense mutation W279*, rst reported in association with a Portuguese founder haplotype, was the most frequent mutation, representing 66% of all mutated alleles. 27 During the period of the clinical evolution of AOA1, the rst disease symptoms correlate with poor coordination and ataxia.…”
Section: Introductionmentioning
confidence: 97%
“…[4][5][6][7][8] Acquired causes of ataxia such as alcoholism, vitamin de ciencies, multiple sclerosis, vascular disease, meningitis, tumors, paraneoplastic diseases, viral cerebellitis, and cerebellar abscess need to be considered in everyone with ataxia in search of treating the cause with speci c treatment. [9][10][11] Ataxia and Oculomotor Apraxia type 1 (AOA1) is a speci c type of hereditary ataxia found in patients with mutations in the APTX gene and a clinical presentation accompanied by oculomotor apraxia. 1,[12][13][14][15][16] The APTX gene encodes for a protein called Aprataxin, composed of three domains that share distant homology with the amino-terminal domain of polynucleotide kinase 3′-phosphatase (PNKP), with histidine-triad (HIT) proteins and with DNA-binding C2H2 zinc-nger proteins.…”
Section: Introductionmentioning
confidence: 99%
“…We will include studies involving patients with DCA and exclude studies involving individuals with ataxia other than DCA. DCA encompasses a large number of diagnoses,1 which typically are ADSCA,3 SCA,4–6 FA,7 MSA-C,8 SAOA9 and ARSACS 10. SCA is most typically of the SCA1, 2, 3, 6 and 31 subtypes, among others 54.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Neurodegenerative diseases include several forms of movement disorders and dementia and are characterized by a broad clinical spectrum with sometimes overlapping features, which can make it difficult or even impossible to make a correct diagnosis. The autosomal dominant spinocerebellar ataxias (SCAs) comprise a highly heterogeneous group of rare movement disorders characterized by progressive cerebellar ataxia variably associated with pigmentary retinopathy, ophthalmoplegia, dementia, seizures, pyramidal and extrapyramidal signs, lower motor neuron signs, or peripheral neuropathy 1,2 . Pathogenic variants in about 30 genes have been linked to autosomal dominant forms of cerebellar ataxias 3 .…”
mentioning
confidence: 99%